THE INFLUENCE OF PROVIDING EDUCATION ABOUT EARLY DETECTION OF CERVICAL CANCER ON KNOWLEDGE IN WOMEN OF CHILDBEARING AGE - Rusmalina Agus; Yulis Marita; Fera Novitry; Eka Joni Yansyah (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Cervical cancer is a serious reproductive health issue for women, especially in Indonesia. Early detection through methods such as IVA (Visual Inspection with Acetic Acid) and pap smear is crucial to reduce the morbidity and mortality rates of cervical cancer. However, the coverage of early detection in Indonesia remains low, including in Muara Enim Regency. Education on early detection of cervical cancer is needed to increase the knowledge and awareness of women of childbearing age (WUS). This study aims to determine the effect of education on early detection of cervical cancer on the knowledge of women of childbearing age in Lubuk Empelas Village, working area of Muara Enim City Health Center. This study used a pre-experimental design with a one group pretest-posttest design approach. The sample consisted of 64 women of childbearing age selected through accidental sampling. Data were collected through questionnaires before and after education using the audio-visual method. Data analysis was performed using the paired t-test. The results showed a significant increase in the knowledge of women of childbearing age after receiving education. The average knowledge score before education (pre-test) was 4.0625, while after education (post-test) it increased to 7.5156. The statistical test results showed a p-value = 0.000, indicating a significant effect of education on increasing knowledge. Education on early detection of cervical cancer using the audio-visual method significantly increased the knowledge of women of childbearing age in Lubuk Empelas Village. It is recommended that the Muara Enim City Health Center enhance health promotion efforts using audio-visual media to increase public awareness and knowledge about early detection of cervical cancer.